Synthesis and cytotoxicity evaluation of N-(2-oxo-2-((5-(trifluoromethyl)-1,3,4-thiadiazol-2-yl)amino)ethyl)-2-phenylacetamide derivatives as apoptosis inducers with potential anticancer effects - Ramezani, Farzad; Aliabadi, Alireza; Mohammadi Farani, Ahmad (International Pharmacy Acta, 2018)
Introduction: The statistics show that the numbers of cancer reports is increasing and need for development of new anticancer drugs is a principal aim in current medicinal chemistry. Due to very limitations of current antineoplastic therapeutics such as high incidence of adverse effects and intuitive resistance of tumor, discovery of new anticancer agents feel to be crucial. Methods and Results: Synthesis and cytotoxicity assessment of 1,3,4-thiadiazole derivatives led to the discovery of new compounds with potential anticancer activity. MTT assay was done against three cancerous cell lines containing PC3 (prostate carcinoma), HT-29 (human colon adenocarcinoma) and SKNMC(neuroblastoma) in comparison with doxorubicin as reference drug. All synthesized compounds were identified using spectroscopic techniques like 1HNMR, IR and MS. The synthesized derivatives were afforded with high yields. All target compounds were tested against MCF-7 (breast cancer), H1299 (non-small cell lung carcinoma), A2780 (ovarian carcinoma). Tested derivatives exhibited favorable anticancer activity in vitro compared to doxorubicin in MTT assay. Various derivatives such as Cl, Br, CH3 and F substituents were the best moieties for para positions of the phenyl ring (less than 1 µM). Some of tested compounds with these moieties showed superior activity than doxorubicin. Caspases activation was also explored for tested derivatives. Conclusions: The 1,3,4-thiadiazole derivatives that prepared in the current project displayed significant anticancer activity and apoptosis induction. These agents could be proposed as novel anticancer lead compounds.